Social Entrepreneurship in Sustainable Tourism: A Bibliometric Analysis of Governance, Resilience, and Regenerative Tourism Research - Fitri Wulandary; Asmar Yulastri; Yuliana Yuliana; Yudha Aditya Fiandra; Julia Adelina (Pusat Riset dan Inovasi Nasional, 2026)
This study investigates the intellectual evolution of social entrepreneurship research within sustainable tourism through a bibliometric analysis of Scopus indexed publications published between 2019 and 2026. The study aims to identify dominant research themes, conceptual structures, and emerging sustainability trajectories shaping the relationship between tourism and social entrepreneurship. Bibliographic data were collected from the Scopus database using a structured search strategy and screened following the PRISMA 2020 framework. A total of 80 journal articles were analyzed using Bibliometrix, Biblioshiny, and VOSviewer to examine publication trends, keyword co occurrence, citation structures, and thematic interconnections. The findings demonstrate a significant expansion of tourism social entrepreneurship research, particularly following the post pandemic transformation of global tourism systems. The intellectual structure of the field is increasingly dominated by themes related to governance, resilience, social innovation, community empowerment, and regenerative tourism. The co occurrence network further reveals growing interdisciplinary convergence among sustainability science, governance studies, resilience theory, innovation research, and community based tourism perspectives. The findings indicate that social entrepreneurship is progressively evolving from a market oriented entrepreneurial concept toward a governance oriented sustainability mechanism embedded within broader processes of social ecological transformation and adaptive tourism development. The study contributes theoretically by repositioning social entrepreneurship within a sustainability transition and adaptive governance framework while identifying regenerative tourism and resilience based governance as important future research trajectories within sustainable tourism scholarship.